Religious And Spiritual Dimensions In Moulana Zafar Ali Khan's Poetry - Zeenat Bibi , Dr. Raheela Bibi , Dr. Rukhsana Bibi , Dr. Muhammad Nasir Afridi , Dr. Saeed Ur Rahman , Rubina Gul (Migration Letters, 2024)
Moulana Zafar Ali Khan is a figure in the subcontinent of India and Pakistan whose various aspects are immortalized in history. He was a journalist, poet, translator, political activist, and a national leader; in all these roles, he is regarded with great respect. Each of his roles has a complete dimension. The factors contributing to his comprehensive personality include the circumstances of his time, his teachers, and the significant personalities of his era, which cannot be overlooked. Additionally, the influence of Aligarh is deeply embedded in his persona, [1]and its essence can be simultaneously felt in his thoughts and actions. He was born in 1873 in a small village near Sialkot in Punjab (adjacent to railway station Siddhara Tehsil Wazirabad). He was initially associated with his father Maulvi Sirajuddin's newspaper Zamindar. According to his father's advice, even after his death, he ran this newspaper successfully. His editorials have a distinct identity for newspapers. Who are the torchbearers for the people associated with journalism. He practically raised his voice for the Muslims of India from every platform in journalism, politics, religion and as a writer.